Coordinated, network-based research as a strategic component of science in Brazil - Simpson, Andrew J.G.; Camargo, Anamaria A.; Ferro, Jesus Aparecido [UNESP]; Parra, Jucara; Vasconcelos, Ana Tereza (My University, 2004)
Scientific research plays a fundamental role in the health and development of any society, since all technological advances depend ultimately on scientific discovery and the generation of wealth is intricately dependent on technological advance. Due to their importance, science and technology generally occupy important places in the hierarchical structure of developed societies, and they receive considerable public and private investment. Publicly funded science is almost entirely devoted to discovery, and it is administered and structured in a very similar way throughout the world. Particularly in the biological sciences, this structure, which is very much centered on the individual scientist and his own hypothesis-based investigations, may not be the best suited for either discovery in the context of complex biological systems, or for the efficient advancement of fundamental knowledge into practical utility. The adoption of other organizational paradigms, which permit a more coordinated and interactive research structure, may provide important opportunities to accelerate the scientific process and further enhance its relevance and contribution to society. The key alternative is a structure that incorporates larger organizational units to tackle larger and more complex problems. One example of such a unit is the research network. Brazil has utilized such networks to great effect in genome sequencing projects, demonstrating their relevance to the Brazilian research community and opening the possibility of their wider utility in the future.
Keywords: Brazil; Genome; Network; Sequencing; biomedicine; conference paper; gene sequence; health care organization; health science; investment; research; science; social evolution; technology; genome; human; information service; organization and management; Biological Sciences; Humans; Information Services; Research